Atmospheric aerosols in Huancayo and their relationship with the surface temperature in the Huaytapallana glacier (LACCEI, 2024)
The snow cover on the Huaytapallana glacier is the main source of water for the Mantaro Valley. Many studies have shown that increased aerosols can lead to reduced snow cover. This study focuses on evaluating the changes in atmospheric aerosols during the winter and summer seasons in Huancayo and their relationship with the surface temperature in the Huaytapallana glacier. For this reason, measurements of the optical properties of atmospheric aerosols have been carried out using a CIMEL sun photometer from the AERONET network at the Huancayo Observatory, from January 2018 to March 2022. Likewise, the MODIS sensor belonging to the TERRA satellite was obtained, to obtain the aerosol optical thickness and surface temperature at a spatial resolution of 10km and 5km respectively with a temporal resolution on a monthly basis during the period 2001-2020. In the results obtained, the mean value of EOA for the study period is 0.21 ± 0.07 and the mean alpha value is 1.7 ± 0.22, indicating the presence of fine fashion aerosols. (burns biomass) . Likewise, the main types of aerosols: dust (30%), mixture (23%) biomass (16%), maritime (14%), contaminated (11%), continental (6%). It is concluded that the glacier retreat is - 80% and the increase in atmospheric aerosols is 0.01% EOA day-1 using the CIMEL sun photometer and 0.16% EOA year-1 using the MODIS sensor. With the present investigation, continuous monitoring of forest fires will be proposed to prevent the increase of atmospheric particles, it is also necessary to implement air quality management measures for the Mantaro Valley or at the national level to reduce forest fires as a result of agricultural activities.